The Impact of Arabic Poetry and Proverbs in Teaching English to Non-Native Speakers (Journal of the College of Education for Women, 2019)
Knowledge of literature is an integral part of learning any spoken language. Learning literature expands the learner’s ability to understand the language studied. The field of literature is wide and cannot be limited to poems. It includes the etiquettes of a language and its environment, customs, and traditions etc. The Arabic language is among the languages with a centuries old history. It has achieved remarkable record accomplishments since the pre-Islamic era through to the present. This development is clear evidence of the great importance of literature in the revival of the Arabic language through different eras. As such, in Malaysia and other non-Arabic speaking countries, literature is taught in most schools, institutions and universities that offer Arabic language programs as a means to achieve many goals including developing a literary taste for the Arabic language particularly in its native environment.